IR Vibration and Characterization of All L–Arginine Chlorides - Sukiasyan, R. P.; Apreyan, R. A.; Danghyan, A. A.; Bezhanova, L. S.; Suponitsky, K. Yu.; Atanesyan, A. K.
The reaction of L–arginine with hydrochloric acid (HCl) in water solvent at 0–33°C temperature was investigated in detail in this study. In total, five compounds were successfully obtained and identified, of which L–Arg·HCl (P1), L–Arg·HCl (P21), L–Arg·HCl·H2O (P21), L–Arg·2HCl·H2O (P212121) were known, and L–Arg·2HCl (new) crystal was a novel finding in this study. The conditions for the formation of all compounds were described in this study․Moreover, we present and compare the FT–IR ATR spectra and other properties of all obtained crystals from the L–Arg+HCl+H2O and L–Arg+HBr+H2O systems. The novel compoundL–Arg.2HCl (new) compound contains two double–charged crystallographically independent argininium(L–Arg2+) cations and four chloride ions in a unit cell.
Keywords: Physics